Strategies for improving ASEAN MSME competitiveness by applying digital marketing, business management quality and crowdfunding by applying product innovation and operational efficiency as intervening variables - Hadi, Dwi Prastiyo; Sumastuti, Efriyani; Indriasari, Ika; Fathurachman, Chadyan (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze strategies to improve the competitiveness of micro, small, and medium enterprises (MSMEs) in the ASEAN region through the application of digital marketing, business management quality, and crowdfunding. It also emphasizes product innovation and operational efficiency as intervening variables that mediate the direct influence of these strategies on enhancing MSME competitiveness. Using a mixed methods approach, which combines quantitative and qualitative techniques, the study seeks to provide a comprehensive understanding of strategies to improve MSME competitiveness in the ASEAN region. The results indicate that digital marketing, quality business management, and crowdfunding significantly contribute to product innovation and operational efficiency. These two intervening variables, in turn, positively impact MSME competitiveness in regional and global markets. The findings highlight the importance of integrating technology and innovation-based strategies as the foundation for sustainable MSME development in the digital era.